The Influence of Audiovisual Educational Media on the Knowledge and Attitudes of Female Adolescents at SMUN 5 Pekanbaru regarding Breast Self-Examination (SADARI) - Wahyuni, Rika Sri; Andriani, Andriani; Batubara, Hamidah Sari (International Journal of Public Health Excellence (IJPHE), 2024)
The incidence of breast cancer has increased and is ranked first in relation to cancer in Indonesia and is one of the leading causes of death due to cancer with the number of new cases reaching 68,858 cases. This incident can be prevented by early detection which can be done by self-breast examination. The purpose of this study was to see whether there was an influence of audio-visual educational media on the knowledge and attitudes of female adolescents at SMAN 5 Pekanbaru regarding self-breast examination (SADARI). This study was conducted using a quasi-experimental method with a sample size of81 people were taken by proportioned stratified random sampling. The analysis was conducted using the Wilcoxon test. The results obtained were that there was an influence of audiovisual educational media on the Knowledge and Attitudes of adolescent girls with a pvalue of 0.000 for knowledge and 0.000 for attitudes. It is hoped that in the future the provision of information can be done using audiovisual media.